C. S. Lewis. The Boy Who Chronicled Narnia. A Biography. By Michael White.The Narnian. The Life and Imagination of C. S. Lewis. By Alan Jacobs.C. S. Lewis. A Short Introduction. By Philip Van der Elst.The Way into Narnia. A Reader's Guide. By Peter J. Schakel - Murdoch, Brian (Literature and theology, 2006)
In his autobiography, Surprised by Joy, in 1955, C. S. Lewis drew attention to the fact that there were episodes that he was deliberately omitting. Even so, that autobiography, his diaries and those of his brother, and a great number of his letters (two large volumes of Walter Hooper's definitive edition have now appeared, but plenty were available in various collections) all mean that the facts of his life are mostly very well-known indeed. A biography appeared in 1974 (since revised) and there have been many others since, notably those by George Sayer in 1988 and A. N.